Tissue features of lipid peroxidation in rats in conditions of the long-term influence of oxyethylized nonylphenols and their derivatives. - Marakushin, D. I. (Medicni Perspektivi, 2015)
The research of LPO state of white rats in conditions of the long-term influence of oxyethylized nonylphenols and their derivatives was carried out. It was established, that oxyethylized nonylphenols on day 45 of influence in the doses of 1/10 and 1/100 DL50 caused the increase of diene conjugates, TBA-reactants, Schiff bases content in the blood, liver and brain gomogenate. The latter, because of a high reactogenic capability, probably, plays the role of a basic link limiting stability of an organism to the long-term influence of the studied compounds due to change of physicochemical properties of cellular membranes, activity of membrane-localized and lipid-depending enzymes, reactivity of neuroendocrine, immune and other systems of an organism. Intensification of LPO processes is one of the pathogenic links of the mechanisms of action of oxyethylized nonylphenols and their derivatives; this is necessary to take into account developing methods of their correction.